The Spectrum of seven preventable Diseases at the Pediatric ward of Dr. Pirngadi Hospital Medan - T. Razif; Yahya G. Lubis; T. Murad El-Fuad; Syahril Pasaribu; Chairuddin P. Lubis (Paediatrica Indonesiana, 1993)
A retrospective study on seven preventab!e diseasee was done in 1989. We found 137 (7.1%) cases of all admissions; they were distribued into 12 neonatal tetanus (8.8%), 57 tetanus (4 1.6%), 17 measles (72.1%), 15 diphtheria (10.9%), 35 pulmonary tuberculosis (25.6%), and 7 poliomyelitis (0. 7%). There was no admittance of pertussis; 62% of those cases consisted of under five-year-old children. None of those patients had had measles immunization, and their mothers had not had tetanus toxoid immunization when they were pregnant. The mortality were as follows: neonatal tetanus 4 (33.3%), tetanus 3 (5.3%), measles 1 (5.9%), pulmonary tuberculosis 9 (25.7%) and diphtheria 7 (46.7%).